Pattern of Skull Fracture in Central Southern Region of Nepal - Sanjay Kumar Sah,; Abhishek Karn,; Prakash Chandra Panjiyar,; Haribodhan Joshi, (Janaki Medical College Journal of Medical Science, 2025)
Background & Objectives: Skull is the important structure which covers one of the vital organs, brain. Fracture of skull may lead to trivial to serious types of brain injury. So, this study aimed to observe pattern of skull fracture in a tertiary care hospital.Material and Methods: Descriptive cross-sectional study was carried out among 248 patients visiting to the emergency and neurosurgery department of National Medical College having skull fracture. Data have been collected from history and examinations and radiological investigations. The data were collected by using proforma. Statistical analysis was performed using SPSS 22.0Results: Road traffic accident (51.6%) was the major mode of injury causing skull fracture followed by fall from height (17.5%) and physical assault (13.7%). Vault fractures were seen in 65.6% of subjects. Linear fracture fractures were observed in 147((51.7%) followed by depressed fractures 51(17.9%). Temporal bone fractures were present in 97(34%) of subjects followed by frontal bone fractures 40 (14%).Conclusion: Vault fractures were commonly observed among the skull fracture. Linear fracture was seen in majority of subjects. The most common bone involved was temporal bone.